2016
DOI: 10.1159/000443103
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Anesthetics, Propofol and Sevoflurane, on Liver Ischemia/Reperfusion Injury

Abstract: Background: Propofol and sevoflurane are widely used in clinical anesthesia, and both have been reported to exert a protective effect in organ ischemia/reperfusion (IR). This study aims to investigate and compare the effects of propofol and sevoflurane on liver ischemia/reperfusion and the precise molecular mechanism. Methods and Materials: Rats were randomized into four groups: the sham group, I/R group, propofol treatment group (infused with 1% propofol at 500 µg· kg-1· min-1), and sevoflurane treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 46 publications
0
52
0
1
Order By: Relevance
“…Studies have shown that oxidative stress drastically increases upon reperfusion [35,36] and as such administration of CeO 2 nanoparticles 1h prior to ischemia would result in bioaccumulation of CeO 2 nanoparticles in liver and scavenge ROS that have been generated during reperfusion. While we did not measure the levels of ROS directly, we investigated markers of increased ROS to assess the therapeutic effect of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that oxidative stress drastically increases upon reperfusion [35,36] and as such administration of CeO 2 nanoparticles 1h prior to ischemia would result in bioaccumulation of CeO 2 nanoparticles in liver and scavenge ROS that have been generated during reperfusion. While we did not measure the levels of ROS directly, we investigated markers of increased ROS to assess the therapeutic effect of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Brief episodes of ischemia and reperfusion applied either before (ischemic preconditioning) or after (ischemic postconditioning) prolonged ischemia protects the hearts against myocardial I/R in non-diabetes. Similarly, administration of anesthetics such as sevoflurane, isoflurane, and propofol before or after prolonged ischemia confers cardioprotection against myocardial I/R injury, which is called anesthetic conditioning [3, 4]. However, accumulating evidences showed that the cardioprotective effects of ischemic preconditioning, ischemic postconditioning, or anesthetic conditioning were attenuated or abolished in hearts from diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Sevoflurane have been widely applied in clinical and exposed many problems [26]. The results of this study provide evidence for a novel mechanism underlying sevoflurane induced cognitive function affects phosphorylation of all substrates listed including CDK5 (Fig.…”
Section: Discussionmentioning
confidence: 56%